Pengaruh Permainan Multifunction Cups terhadap Keterampilan Sosial Anak di Taman Kanak-Kanak Jam’iyyatul Hujjaj Bukittinggi - Putri; Yaswinda; Lili Mulyani; Serli Marlina; Resti Elma Sari (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
The social aspect is one of the most essential dimensions in early childhood development. This study aims to determine the effect of the Multifunction Cups game on the development of social skills in early childhood at Jam’iyyatul Hujjaj Kindergarten, Bukittinggi. The research was conducted during the 2025/2026 academic year using a quantitative approach with a quasi-experimental design. The sample consisted of 30 children divided into an experimental group and a control group. The experimental group received treatment using the Multifunction Cups game, while the control group played Lego as usual. Data analysis using SPSS 25 showed that the pre-test results were not significantly different (Sig. 0.532), while the post-test results showed a significant difference (Sig. 0.000). These findings indicate that the Multifunction Cups game has a significant effect on improving children's social skills.